Microhabitat change drives diversification in pholcid spiders - Eberle, Jonas; Dimitrov, Dimitar; Valdez-Mondragón, Alejandro; Huber, Bernhard A. (BMC evolutionary biology, 2018)
Microhabitat changes are thought to be among the main drivers of diversification. However, this conclusion is mostly based on studies on vertebrates. Here, we investigate the influence of microhabitat on diversification rates in pholcid spiders (Araneae, Pholcidae). Diversification analyses were conducted in the framework of the largest molecular phylogeny of pholcid spiders to date based on three nuclear and three mitochondrial loci from 600 species representing more than 85% of the currently described pholcid genera. Assessments of ancestral microhabitat revealed frequent evolutionary change. In particular, within the largest subfamily Pholcinae, numerous changes from near-ground habitats towards leaves and back were found. In general, taxa occupying leaves and large sheltered spaces had higher diversification rates than ground-dwelling taxa. Shifts in speciation rate were found in leaf- and space-dwelling taxa. Our analyses result in one of the most comprehensive phylogenies available for a major spider family and provide a framework for any subsequent studies of pholcid spider biology. Diversification analyses strongly suggest that microhabitat is an important factor influencing diversification patterns in pholcid spiders.